Performance evaluation of an M/G/n-type queue with bounded capacity and packet dropping - Tikhonenko, Oleg; Kempa, Wojciech M. (Zielona Góra: Uniwersytet Zielonogórski)
A queueing system of the M/G/n-type, with a bounded total volume is considered. It is assumed that the volumes of the arriving packets are generally distributed random variables. Moreover, the AQM-type mechanism is used to control the actual buffer state: each of the arriving packets is dropped with a probability depending on its volume and the occupied volume of the system at the pre-arrival epoch. The explicit formulae for the stationary queue-size distribution and the loss probability are found. Numerical examples illustrating theoretical formulae are given as well.
Keywords: AQM algorithms; finite buffer; loss probability; total packet volume; queue-size distribution